Drivers of local densities of endangered Lycaena helle butterflies in a fragmented landscape. Issue 4 (4th September 2015) - Nabielec, Joanna; Nowicki, Piotr
Abstract: Due to their specialised habitat requirements, butterflies are particularly vulnerable to habitat loss and fragmentation. Understanding the drivers of local abundances of species is essential for their effective conservation in fragmented landscapes. We investigated factors affecting population densities of an endangered European butterfly, the Violet Copper ( Lycaena helle ), occurring in a small metapopulation near the city of Kraków, southern Poland. The environmental parameters tested as predictors of the local densities of the species included both the variables associated with spatial structure of habitats such as patch sizes, their isolation and fragmentation as well as those potentially reflecting habitat quality. Patch area and vegetation height turned out to be the only factors significantly influencing L. helle densities, both having a positive effect. The positive impact of patch area is a bit surprising, since its relationship with population densities is typically negative in butterflies. In our study system it is likely to derive from source‐sink dynamics as the smaller habitat patches are apparently too small to sustain viable local populations. In turn, the positive influence of vegetation height implies that the ongoing succession does not deteriorate the quality of the recently abandoned meadows yet, whereas higher turf may provide better sheltering places. The loss of almost half of L. helle habitat patches in the study area in recent years is alarming. However, its inclusion into the Natura 2000 system should help to conserve the species as long as this act is followed by proper management of its habitats.